PENGARUH RELAKSASI OTOT PROGRESIF TERHADAP PENURUNAN TEKANAN DARAH PADA LANSIA DENGAN HIPERTENSI DI DUSUN IV TANJUNG ANOM MEDAN TAHUN 2018 - Indra Hizkia P; Ance Siallagan; Mega Tresna Hulu (Elisabeth Health Jurnal, 2018)
Hypertension in the elderly is characterized by an increase in systolic and diastolic blood pressure of ≥ 140/90 mmHg persistently and often occurs in ± 55 years old elderly. Progressive Muscle Relaxation is one technique that can relax muscle tension and create a relaxed feeling that can lower blood pressure. Goals : This study aims to determine the effect of progressive muscle relaxation on blood pressure decrease in elderly with hypertension in Dusun IV Tanjung Anom Medan Year 2018. Methods : The design used design is one group pretest and post test design with purposive sampling method that is 28 respondents elderly who are in Dusun IV Tanjung Anom Medan. The Instruments used for taking data were SOP, observation sheet, stethoscope, sphygmomanometer Result : Data analysis showed the result of pre intervention blood pressure mostly on 1st degree of hypertension 16 people (57,1%) and post intervention mostly on 2 prehypertension were 13 people (46,4%). The result of Wilcoxon Sign Rank Test statistic shows that p = 0,000 (p <0,05) means the effect of progressive muscle relaxation on blood pressure drop in elderly with hypertension in Dusun IV Tanjung Anom Medan Year 2018. Conclutions : The result of this study is expected elderly able to apply this progressive muscle relaxation routinely.